X(x+3)=x(x+6)-15

Simple and best practice solution for X(x+3)=x(x+6)-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(x+3)=x(x+6)-15 equation:


Simplifying
X(x + 3) = x(x + 6) + -15

Reorder the terms:
X(3 + x) = x(x + 6) + -15
(3 * X + x * X) = x(x + 6) + -15
(3X + xX) = x(x + 6) + -15

Reorder the terms:
3X + xX = x(6 + x) + -15
3X + xX = (6 * x + x * x) + -15
3X + xX = (6x + x2) + -15

Reorder the terms:
3X + xX = -15 + 6x + x2

Solving
3X + xX = -15 + 6x + x2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Reorder the terms:
15 + 3X + -6x + xX + -1x2 = -15 + 6x + x2 + 15 + -6x + -1x2

Reorder the terms:
15 + 3X + -6x + xX + -1x2 = -15 + 15 + 6x + -6x + x2 + -1x2

Combine like terms: -15 + 15 = 0
15 + 3X + -6x + xX + -1x2 = 0 + 6x + -6x + x2 + -1x2
15 + 3X + -6x + xX + -1x2 = 6x + -6x + x2 + -1x2

Combine like terms: 6x + -6x = 0
15 + 3X + -6x + xX + -1x2 = 0 + x2 + -1x2
15 + 3X + -6x + xX + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
15 + 3X + -6x + xX + -1x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 1.4+(2.3)= | | Xsquare+3x-4=0 | | 3500+1680x=220650 | | P-19=17 | | 12=-6k+4+2 | | 3a^2+30a+100=0 | | -8=-3k-5k | | log(8x+2)=6 | | -18=5x+4x | | 7(11+1)+5(11+1)=14 | | 3a-5a=8 | | 7(-13+1)+5(-13+1)=14 | | 2n+5+7n=-4 | | x+60=10 | | 6v+7v=-13 | | m+3-7m=-15 | | 6x+64=9x+7 | | xy+5x-y-10=0 | | 1/2x=3/2x-7 | | 7(x+1)+5(x+1)=14 | | -11=n-1+n | | 4x^6+45=40 | | 6x-4+4x=-14 | | 3x-10=10x | | 8+7n-4n=-1 | | z^2(2y)/(3) | | -3(3+8j)= | | n-6-2=-2 | | z^2(2|y)/(3) | | 5+17x-3=9x+12-2x | | -5=6+7x+3 | | x+9*2x=0 |

Equations solver categories